Pengaruh Motivasi Kerja, Lingkungan Kerja, dan Disiplin Kerja Terhadap Kinerja Karyawan di PT Asuransi Bhakti Bhayangkara Jakarta Selatan - Niwang Sari Abidin, Endang Sri Paras Titi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines how work motivation, work environment, and work discipline collectively influence employee performance at PT Asuransi Bhakti Bhayangkara. This study uses a quantitative survey method and involves 35 employees from the Human Resources Division and Marketing Division. The study analyzes three main independent variables: motivation (X1), measured through job satisfaction, engagement, and employee turnover rates; work environment (X2), evaluated based on factors such as leadership, communication, and development opportunities; and work discipline (X3), assessed through attendance, compliance, and behavior. Based on the t-test, variables X1 (t=2.126 1.692), X2 (t=1.853 1.692), and X3 (t=3.087 1.692) significantly influence Y. The F-test shows Fcalc 37.174 Ftab 2.874 with SIG 0.000. Thus, Ha is accepted and Ho is rejected, both partially and simultaneously. These findings emphasize that employee performance is not shaped by a single factor but through the interaction between motivation, environment, and discipline. Therefore, efforts to improve performance must consider these aspects comprehensively, and companies must strive to support the development of employees who possess these aspects. This study highlights the need for a comprehensive organizational strategy that simultaneously enhances motivation, creates a supportive work environment, and maintains high standards of discipline to effectively improve employee performance